Factors of socio-psychological maladaptation in individuals with deviant behavior - KIKBAEV, Daniar (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. This article is relevant because it aims to establish the relationship between socio-psychological maladaptation factors and predisposition to deviant behavior. Its goal is to demonstrate through empirical research that a tendency toward specific types of deviant behavior is linked to the components of aggressiveness and hostility, leading to a breakdown in an individual’s socio-psychological adaptation. Methods. Three standardized questionnaires were utilized: the Socio-Psychological Adaptation Diagnostic by K. Rogers-R. Diamond, the method for assessing the tendency toward deviant behavior (A. N. Orel), and the predisposition to aggression and hostility by A. Buss-A. Durkee. The sample consisted of 252 participants (n = 252), aged 21 to 46, who provided consent to participate. Results. Factors that predispose individuals to deviant behavior are either directly connected to adaptive factors or stimulate abnormal increases in aggressiveness and hostility. Such alterations result in impaired adaptability. Empirical data suggest that the psychological profile of a person with a deviant orientation results from socialization disorders. Conclusions. The most significant finding is the interdependence between adaptation factors and factors related to aggressiveness and hostility. Strong correlations between predisposition to deviant behavior and the components of aggressiveness and hostility may be critical in determining the extent of social maladaptation in a person with a deviant orientation. The key elements influencing socio-psychological maladaptivity are the tendencies toward deviant behavior amid abnormal levels of aggressiveness and hostility. Conversely, lowering aggressiveness and hostility levels can balance the primary factors affecting adaptability and normalize indicators related to predisposition to deviant behavior. Therefore, normalizing individual psychological traits of adaptability can help decrease the risk of deviant behavior and reduce aggressiveness and hostility.